What Every Teacher Should Know about Joe Crosswhite - Kasten, Margaret "Peggy"; Schultz, James E. (Ohio Journal of School Mathematics, 2020)
The authors discuss the life and legacy of Dr. F. Joe Crosswhite, a mathematics educator whose work has had a profound impact on the lives of countless students and colleagues.  As NCTM president (1984-86), F. Joe Crosswhite oversaw the approval of the basic design and initial financing for what became the Curriculum and Evaluation Standards for School Mathematics.  Crosswhite also made significant contributions to the influential Second International Mathematics and Science Study. He played a seminal role in the development of the Mathematical Sciences Education Board and chaired the Conference Board of the Mathematical Sciences.